Pengaruh Kecepatan Gesek dan Ukuran Serbuk Cangkang Kelapa Sawit Terhadap Laju Keausan Material Komposit Alam - Mastariyanto Perdana (TRAKSI, 2021)
Composite materials have been very widely applied in the industrial, one of its applications is on motorcycle brake pads. Composites that were applied to motorcycle brake pads still tend to use metal-type composite materials. They were made from synthetic materials. In this study, the use of oil palm shell waste as a composite base material was expected to be applied as an alternative material for motorcycle brake pads. In terms of hardness, the oil palm shell has high hardness. The purpose of this study was to determine the effect of friction speed and size of palm oil shell powder on the wear rate of natural composite materials. The matrix used in this study was an epoxy, one of polymer material. The volume fraction between oil palm shell powder and epoxy resin was 55%: 45%. The variations in the size distribution of oil palm shell powder were 841-595 µm, 595-420 µm and 420-297 µm. Composite manufacturing process using compression molding method. The test carried out in this study is the wear rate test with a variation of the friction speed by 1300 rpm, 1500 rpm and 1700 rpm. The results showed that the larger size of palm kernel shell powder with low friction speed in natural composites gave the lowest wear rate value. For oil palm shell powder size 841-595 µm has a wear rate of 3.44 x 10-7 gr/mm2.s at a friction speed of 1700 rpm, 2.50 x 10-7 gr/mm2.s at a friction speed of 1500 rpm and 1.11 x 10-7 gr/mm2.s at a friction speed of 1300 rpm. For palm shell powder size 595-420 µm has a wear rate of 3.89 x 10-7 g/mm2.s at a friction speed of 1700 rpm, 2.67 x 10-7 gr/mm2.s at a friction speed of 1500 rpm and 1.35 x 10-7 gr/mm2.s at a friction speed of 1300 rpm. For oil palm shell powder size 420-297 µm has a wear rate of 4.83 x 10-7 gr/mm2.s at a friction speed of 1700 rpm, 3.52 x 10-7 gr/mm2.s at a friction speed of 1500 rpm and 1.58 x 10-7 gr/mm2.s at a friction speed of 1300 rpm. It is hoped that the composite made from palm oil shell powder and epoxy resin can later become an alternative material for motorcycle brake pads.